1998
DOI: 10.1086/305037
|View full text |Cite
|
Sign up to set email alerts
|

The Norris Survey of the Corona Borealis Supercluster. III. Structure and Mass of the Supercluster

Abstract: We measure the field galaxy luminosity function (LF) as a function of color and redshift from z = 0 to z = 0.5 using galaxies from the Norris Survey of the Corona Borealis Supercluster. The data set consists of 603 field galaxies with 0 < z ≤ 0.5 and spans a wide range in apparent magnitude (14.0 m ∼ < r ∼ < 21.5 m ), although our field galaxy LF analysis is limited to 493 galaxies with r ≤ 20.0 m . We use the observed g − r colors of the galaxies to compute accurate corrections to the rest B AB and r bands. W… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
106
1

Year Published

2001
2001
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(118 citation statements)
references
References 65 publications
11
106
1
Order By: Relevance
“…The results quoted in Table 1 are for A2067 only as determined from our separation ; 200 velocities from Small, Sargeant, & Hamilton (1997) have been included in this analysis of the clusters A2067 and A2061. Small et al (1998) discuss the structure and dynamics of the larger supercluster.…”
Section: A1749mentioning
confidence: 99%
“…The results quoted in Table 1 are for A2067 only as determined from our separation ; 200 velocities from Small, Sargeant, & Hamilton (1997) have been included in this analysis of the clusters A2067 and A2061. Small et al (1998) discuss the structure and dynamics of the larger supercluster.…”
Section: A1749mentioning
confidence: 99%
“…Morphologically SCl 094 is a multispider with a number of clusters connected by low density filaments, with an overall very elongated shape that resembles a horse-shoe, with the merging X-ray cluster A2065 at the top (Chatzikos et al 2006). SCl 094 has been studied by Small et al (1998), who found that the core of this system probably has started to collapse. Numerical simulations show that such collapsing cores in superclusters are rare (Gramann & Suhhonenko 2002).…”
Section: Notes On Individual Superclustersmentioning
confidence: 99%
“…The structure of the superclusters is formed during a hierarchical evolution where the high-density cores of superclusters are older and dynamically more evolved than outskirts regions. While full rich superclusters are not bound systems, their high-density cores may collapse at present or in the course of the future evolution (Small et al 1998;Reisenegger et al 2000;Rines et al 2002;Nagamine & Loeb 2003;Proust et al 2006;Dünner et al 2006;Luparello et al 2011;Pearson et al 2014;Chon et al 2015;O'Mill et al 2015;Einasto et al 2015;Gramann et al 2015). This makes galaxy superclusters unique objects to study their properties and the properties and evolution of the galaxy systems (groups, clusters, and filaments) inside the dynamically evolving environment of superclusters.…”
Section: Introductionmentioning
confidence: 99%